Raising mentally strong kids : how to combine the power of neuroscience with love and logic to grow confident, kind, responsible, and resilient children and young adults - Amen, Daniel G.; Fay, Charles, 1964- (Tyndale Refresh, 2024)
A #1 New York Times bestselling author and neuropsychiatrist and a child psychologist team up in this groundbreaking book that gives parents practical tools to help them raise mentally healthy kids who are equipped to thrive.